(untitled) (The Research of Medical Science Review, 2024)
This study explores the relationship between resilience and the quality of life (QoL) among burn injury patients, focusing on how resilience impacts their psychological, physical, and social recovery. Data were collected from 370 participants, including demographic variables such as age, gender, marital status, education level, income, household status, and family structure. Statistical analyses, including independent samples t-tests and one-way ANOVA, revealed significant differences in resilience based on these variables. Specifically, younger patients (ages 18-30) exhibited 45% higher resilience compared to those aged 45 and above. Married participants demonstrated 35% higher QoL scores, while individuals with higher educational levels (bachelor's degree and above) showed 50% better resilience. Higher income groups reported 40% better psychological and social outcomes. Resilience was also found to correlate with improved psychological outcomes, as patients with high resilience were 60% more likely to report positive emotional health and better coping mechanisms. These findings emphasize the importance of resilience as a protective factor in burn recovery, suggesting that healthcare providers should integrate resilience-building interventions into treatment protocols to enhance patient outcomes. Tailored interventions focusing on psychological and social support can promote resilience and improve QoL for burn patients, thus facilitating their rehabilitation and reintegration into daily life